Ivermectin A Potential Treatment In Covid-19, Related to Critical Illness - Rashid Qadeer, Syed Muhmmad Kashif, Darshan Kumar, Madiha Mehmmood, Jawahar Lal, Faizan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the potential use of ivermectin with standard therapy among mild to moderate covid-19 illness. Methods: This is a single-centered, prospective observational, randomized, parallel group (1:1 ratio), standard versus controlled ivermectin study recruited 210 confirmed COVID-19 positive patients who were admitted in COVID treatment center of Dr Ruth Kum Pafu Civil hospital Karachi, Pakistan from 1st November 2020 to 30th May 2021. Data were analyzed using SPSS version Results: Total of 210 patients were enrolled in the study and aged matched patients were divided in two groups 105 patients received ivermectin 6 mg twice a day for five days along with standard therapy while remaining 105 patients received standard therapy as per local and international guidelines. Male were 140(66.7%) and female 70(33.3%); age ranges between 26 to 77 years and majority 140( 66.7%) were more than 50 years of age. Fever, dry cough and dyspnea were the major symptoms seen; 112(53.3%) patients had DM as a comorbid illness . Total of 21(20%) of 105 patients of ivermectin group had negative PCR for COVID 19 on day seven while the other group had positive covid test in all of 105 patients . On day 10 total of 49 more patients from ivermectin group found COVID negative along with 21 previously negative had second PCR was found negative in this way total of 70( 66.7%) of ivermectin group had negative PCR for COVID 19 while 21(20%) patients from non ivermectin got negative PCR for COVID 19 on day 10 . Conclusion: Use of ivermectin with standard therapy clear the virus earlier than standard therapy in mild to moderate COVID-19 infected patients admitted in COVID treatment center of Dr Ruth Kum Pafu Civil Hospital Karachi Keywords: Covid-19, Ivermectin, Standard Therapy .